Product photography assistance for micro, small, and medium enterprises in Banyuasin, South Sumatra - Farisha Sestri Musdalifah; Krisna Murti; Annisa Rahmawati; Januar Eko Aryansah; Harry Yogsunandar (Universitas Muhammadiyah Magelang, 2022)
In this digital era, online trade transactions have become a new culture. Small business owners in Sungai Pinang Village are familiar with technology and have been assisted in expanding the market to the online realm via smartphones. However, the challenge experienced by small business actors is that there are not proper and not attractive product photos to upload to social media and online stores, so they cannot attract the attention of potential consumers. This community empowerment activity aims to assist small business actors in being able to take photos of their business products in marketing and promoting their products digitally. There are 30 business owners attended the workshop with various types of business products. Small business participants were given materials about marketing, promotion, and basic knowledge of product photography. They also participated in workshops and mentoring on making attractive product photos so the photos could be promoted online. In addition, there are follow-up activities by monitoring the social media of small business owners to see the implementation of uploaded product photos in promoting their products. The result of this event is an increase in the general knowledge of small business owners about the basics of product photography so that it can be applied when marketing and promoting their business products online.